The Woodgrain of the Chessboard: A Response to Roy Germano. Issue 3 (September 2014) - Farrell, Henry
<x content-type="archive" xml:space="preserve">Abstract</x> Roy Germano argues for an "analytic filmmaking, " which would use film as a means to elucidate social scientific laws and generalizations. Yet film, even when it seeks simply to document the truth, is a form of narrative. To strip these ambiguities away in the name of a crude empiricism would rob these narratives of just that kind of information that makes them most valuable—the subtleties and nuances that they can capture and that simple transcripts cannot. Better models for understanding film can be found either in the direct acknowledgment and exploration of these ambiguities, or, alternatively, in the "analytic narratives" approach. Unlike Germano's analytic film making, which prizes the abstract over the particular, analytic narratives gather their energy from the continuing tension between the particular and the abstraction.